(Invited) Probing Electronic Transport Properties in Two-Dimensional Materials Using First Principles Calculations - Marcelo A. Kuroda (ECS Meeting Abstracts, 2020)
Heterostructures formed with two-dimensional (2D) materials preserve atomically sharp crystalline interfaces, offering novel platforms for a wide range of applications. Due to their one- to few-atom thickness, quantum mechanical effects and atomistic details play key roles in their properties. Here I will present the use of first principles calculations (density functional theory) to characterize and control electronic and spin transport in systems formed with these layered materials. First, I will describe the underlying mechanisms governing the contact resistance in lateral heterojunctions based on transition metal dichalcogenides ( MX 2 with M = Mo or W and X = Se or Te). By joining semiconducting (2H) and metallic (1T') phases, these lateral structures have been proposed to improve charge carrier injection in these materials with respect to that obtained via direct deposition of metals [1,2]. We find that contact resistance values of < 10 W·cm may be achieved by enhancing the coupling between electrodes in lead and channel via phase engineering. Next, I will describe the features of the mechanical modulation of tunneling current (piezoresistivity) in vertical transition metal dichalcogenide heterostructures [3]. The piezoresistive effect measured in these systems is rationalized in terms of the electronic properties of the electrode (e.g. work function, d-bands, etc.), as well as the junction's thickness and composition. Finally, I will characterize the tunneling magnetoresistances in graphene/chromium trihalides heterostructures that were recently demonstrated experimentally [4]. Our description based on the ballistic transport evince the importance of quantum confinement and interlayer magnetic coupling emerging at these length scales [5]. In addition, our results show remarkable agreement with experimental measurements. The virtues and limitations of these approaches will also be discussed. Acknowledgements: The author gratefully acknowledges the financial support from NSF DMR-1848344 grant. References: [1] R. Kappera et al. , Nat. Mater. 13 , 1128 (2014). [2] S. Cho et al. , Science 349 , 625 (2015). [3] D. Fu et al. , Appl. Phys. Lett. 103 , (2013). [4] T. Song et al. , Science 360 , 1214 (2018). [5] J. J. Heath et al. , arXiv:1910.01102 (2019).